Bimbingan Teknis Pengukuran Kinerja Keuangan pada Kelompok Mahasiswa Peserta Praktik Lapang Perkoperasian di Koperasi Karyawan PT. Perusahaan Listrik Negara Daerah Surakarta - Savitri Dewi, Lely (E-Coops-Day, 2024)
IKOPIN University is the only university that has a cooperative vision in Indonesia and requires students to carry out cooperative field practice with the aim of being directly involved in making observations, identifying problems, analyzing and finding solutions to cooperative problems. Field practice is a forum for students to apply theories obtained from the process of teaching and learning activities during college in the world of work. This activity aims to introduce the real world of work and students can discuss and adapt in a cooperative environment. In accordance with the theme carried out in the field practice for the 2024/2025 academic year, namely “Synergy and Collaboration Student IKOPIN University For Continuity Cooperative From Yogyakarta and Surakarta” which means that collaboration means that all IKOPIN University students are required to practice work through the process of sharing ideas or notions either to achieve the same goal or to solve a problem, especially in cooperatives. Then the meaning of synergy itself refers to a concept which emphasizes that cooperation built by two or more people will produce greater benefit value than working individually. The scope of this technical guidance focuses on assessing the financial performance of cooperatives in terms of liquidity, profitability, solvency and cooperative business performance.